Management of technology the missing link: found - Alina Shamsuddin (Penerbit UTHM, 2014)
The management of technology (MoT) is one of the disciplines which is widely but vaguely known, let alone truly understood and implemented. Therefore it is perhaps not surprising that many organizations are unaware that they are already managing the technology utilized in their respective companies to deliver their products or services in a competent and effective manner! To comprehend and command the powerful tool of MoT will enable enhanced performance of an organization, by mobilizing its talents, potentials and assets in a unified effort towards maximum productivity